2021
DOI: 10.3389/fphar.2021.655836
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immunosuppressive Medication Nonadherence Factors Through a Combined Theory Model in Renal Transplant Recipients

Abstract: Background: Immunosuppressive medication (IM) nonadherence is associated with poor transplant outcomes. Therefore, it is of great importance to identify predictive factors with IM nonadherence. We aimed to improve the predicted capacity of the theory of planned behavior (TPB) by adding health belief model’s (HBM) variables in renal transplant patients (RTPs).Methods: This cross-sectional study distributed questionnaires to patients who had undergone renal transplant and follow-up regularly in the transplant ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…In this study, the IM non-adherence of the patients was 38.5%, and taking IM more than 2 h before or after the recommended dosing time in the last 4 weeks was the most common issure of IM non-adherence, which occurred at a rate of 27.8%. This result was similar to the results of our previous study (5), which also suggested that the problem of medication non-adherence in RTPs remains serious, especially not taking medication on time. Therefore, there is an urgent need to predict the risk factors for IM non-adherence and to undertake targeted intervention methods to improve the situation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the IM non-adherence of the patients was 38.5%, and taking IM more than 2 h before or after the recommended dosing time in the last 4 weeks was the most common issure of IM non-adherence, which occurred at a rate of 27.8%. This result was similar to the results of our previous study (5), which also suggested that the problem of medication non-adherence in RTPs remains serious, especially not taking medication on time. Therefore, there is an urgent need to predict the risk factors for IM non-adherence and to undertake targeted intervention methods to improve the situation.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted in 99 US-based transplant centers showed that 71.1% of health care professionals acknowledged not having a prospective medication non-adherence screening protocol, and little is known about strategies currently utilized by transplant centers to monitor or manage this issue (38). To solve this common problem, some scholars have attempted to establish predictive models of non-adherence in patients after kidney transplantation, such as HBM and TPB models (5,8,20,39). However, models currently constructed has several limitations, such as insufficient coverage variables, inability to quantify risk prediction, inability to be directly applied to clinical practice, and only providing theoretical reference value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of MNA using the BAASIS in KTRs was previously reported to be 34% to 66% and that of the present study was within this range. 13,[28][29][30][31][32][33][34] This prevalence range of MNA using the BAASIS was relatively >36% reported by a previous meta-analysis. 10 This is probably because the BAASIS uses an intentionally strict scoring method and includes timing adherence as a criterion.…”
Section: Discussionmentioning
confidence: 93%
“…HBM is widely employed in health education, such as explaining the transformation and maintenance of various healthy behaviors, or forming an important theoretical framework to guide behavior intervention. HBM is applied through the analysis of individual health beliefs; the use of pictorials, brochures, and WeChat education platform; and other ways to promote the relevant content of healthy behavior, give individuals correct cognition to establish a good health belief, make them take the initiative to complete healthy behavior, and finally achieve the goal of preventing adverse consequences [ 9 ]. Based on this, the current study focuses on the effects of nursing intervention based on HBM on self-perceived burden, drug compliance, and quality of life of renal transplant recipients.…”
Section: Introductionmentioning
confidence: 99%